ГЕНЕЗИС ОСНОВ СТРАХОВОГО ДЕЛА - Клапків, Юрій; Klapkiv, Jurij; Клапкив, Юрий (Изд-во Костром. гос. ун-та, 2017)
the article deals with the questions of Genesis of the foundations of the insurance business allocated to some components. It was found that the formation of the insurance business happens long before the formation of insurance companies. With the release of the insurance business from the trading activities implemented by the formation of key terminology and concepts.
THE GENESIS OF THE BASIC INSURANCE BUSINESS
Keywords: insurance, mutual assistance, transfer of risk, transfer damage, the ketubah, the redemption sum.; страхование, взаимопомощь, трансфер риска, трансфер ущерба, кетуба, выкупная сума.